Do We Need a (New) Theory of Lexicography? - Tarp, Sven (Lexikos, 2012)
In the current transition from printed to electronic dictionaries the question has been raised whether we need a new theory of lexicography that may guide the conception and production of lexicographical e-tools or if we can use the theories already developed in the era of printed works. In order to answer this question the article first of all discusses the question whether a lexicographical theory exists, is possible at all or even wanted. It shows that the various approaches to this question are mainly due to the fact that the very concept of theory is widely disputed within lexicographical circles. In this respect, it briefly discusses the Anglo-Saxon academic tradition according to which science is only related to natural phenomena and where all other phenomena are referred to the spheres of art and craft, and it shows that this tradition is widely opposed by the traditions in other parts of the world. Upon this basis, the article shows that a lexicographical theory is not only possible but that various highly useful theories already exist. Finally, it claims that these theories, especially the ones that are not only focusing on the printed dictionary form, should not be rejected but should be further enhanced and improved in close interaction between lexicography and other consultation disciplines within the broad area of information science.